SOSIALISASI PENDIDIKAN KEPARIWISATAAN KEPADA GURU-GURU PENDIDIKAN ANAK USIA DINI (PAUD) GUGUS JAHAYA JINGGA KAB. BINTAN - Supardi; Haufi Sukmamedian; Syailendra Reza Irwansyah Rezeki (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
The phenomenon of tourism has existed since the existence of human travel from one place to another and its development is in accordance with the socio-cultural community itself. Since then there have also been human needs that must be met during the journey, in addition to the motivation that drives humans to fulfill their needs. With the increase in human civilization, the urge to travel is getting stronger and the needs to be fulfilled are increasingly complex. The motivations and motives for traveling from time to time are of different levels, according to the development and socio-cultural, economic and environmental level of the community itself. The motivations and motives of people's journeys in prehistoric times are different from the motivations and motives of people's journeys in modern times. The way of travel and the facilities used by the community are still simple when compared to more advanced societies.